The Effect of Peer Bullying Booklets on The Cognitive Development of Children - Nurul Lidya; Vera Suzana Dewi Haris (Journal Center of Excellent : Health Assistive Technology, 2023)
The incidence of bullying in children at school is still high. This bullying can affect the psychological and cognitive of students. For this reason, schools and parents need attention in handling it. The purpose of this study was to determine the effect of peer bullying behavior on children's cognitive development at West Cilandak 08 public elementary school, South Jakarta. The design of this research is quantitative research using cross sectional time approach. The population in this study is a total sampling of 65 students. The results of the study were that most of the respondents were 11 years old (58.5), most of the respondents were female (58.5%), most of the respondents had 2 siblings (44.6%). most of the respondents were bullying moderate intensity (46.2%), and most of them were doing verbal bullying (62.8%). Most of them have learning achievement in the bad category of 69.2%. The results of statistical tests obtained P Value of 0.002 > (0.528) so it can be concluded that there is a relationship between bullying and cognitive development of children.